Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
( - 2 - 5m ) / 3
Step-by-step explanation:
15m + 9n = - 6
9n = - 6 - 15m
Divide by 3 on both sides,
9n / 3 = - 6 / 3 - 15m / 3
3n = - 2 - 5m
n = ( - 2 - 5m ) / 3
Answer:
[tex]15m + 9n = - 6 \\ 9n = 15m - 6 \\ n = \frac{15m - 6}{9} \\ \\ n = \frac{15m - 2}{3} [/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.